369 TREMOR IN PATIENTS WITH SEX CHROMOSOME ANEUPLOIDY. Issue 1 (1st January 2007) - Borodyanskaya, M.; Tartaglia, N.; Davis, S.; Ono, M.; Hansen, R.; Hagerman., R.
Abstract : Purpose: Approximately 5% of the general population exhibits essential tremor. In previous case reports, essential tremor has been reported as a clinical feature of children and adults with sex chromosome aneuploidy (SCA). In this study, we have compared the prevalence and characteristics of tremor in patient groups with SCA, including XXY, XYY, XXYY, and XXX syndromes. Methods: A total of 132 individuals with SCA (39 XXY, 54 XXYY, 17 XYY, 22 XXX) between the ages of 1 and 59 were evaluated through a study on health and development in this population. As part of the protocol, subjects received a complete medical history and physical examination. Testing using the CATSYS system was also performed on a subset of patients to quantify characteristics of tremor and neurological functioning. Results: The prevalence of tremor in the SCA groups are as follows: XXY 23%; XXYY 53%, XYY 23%, and XXX 9%. Since the development of tremor is typically age-dependent, we also determined the prevalence of tremor in various age groups for each SCA condition. Small sample sizes in some age groups limits this interpretation. Medication treatment with propranolol was effective in decreasing tremor in 2 XXYY patients. No other patients had received medication treatment targeting tremor. Results of the CATSYS system including degree of resting tremor, intention tremor, reaction time, and fine and gross motor components of tremor will also be presented. Conclusion: Tremor is a common feature in individuals with sex chromosome aneuploidy, especially in males. In XXY and XXYY syndromes, the prevalence of tremor increases with age up to 67% in XXY and 80% in XXYY adolescents or young adults. Males with XYY syndrome also have tremor that presents in early adolescence. The presence of tremor can impact many aspects of daily life, including handwriting, sports, and daily living skills. Further study is needed to further characterize the features of tremor and to identify helpful medication treatments in this population. Because tremor may indicate an underlying neuronal abnormality not yet studied in individuals with SCA, further research is needed to understand the causes of tremor in this population.